A educação inclusiva de alunos com deficiência física: problematizando o corpo no contexto escolar - Finger, Alenia Varela (2007)
The present study, inserted in the Line of Special education, aimed to problemize the role of the body in the perspective of Inclusive Education, contextualizing it in the reality of physically handicapped students, included in the initial grades of the city schools in Caxias do Sul, Rio Grande do Sul state. So, it was first carried out a theoretical search in order to revisit the different perspectives about the body, as well as to put together the discussions related to the Inclusive Education. To learn conceptions and attitudes of participant teachers in the research concerning to the body and inclusive education and to identify the conditions of access of physical space in the studied schools, we made an exploratory study.The field research happened in city schools of Caxias do Sul, Rio Grande do Sul state, that had physically handicapped students - mobility limitation (wheelchair users), included in common classes of inital series, being the participants the five schools and the teachers of those students, indicated by the City Education Secretary (SMED). The instruments for the data collection were the semi-structured interview, applied to the teachers, the sistematic observation of the physical space and the field diary. The collected data obtained with the interviews were analized in accordance with its content and, together with the data taken in the observations, were approached in a quantitave and qualitative manner. Reaching the proposed objectives, we identified the teachers' conceptions and positive attitudes facing the body and the inclusion, predominantly, even though, in some minor situations, we pointed out the fragmentary thought of the subject in body/mind, without the approach of the body in the practice in the classroom; about the body of the include students, we identified initial sentiments of fear and anxiety but these ones were reverted with the knowledge of their physical limitations and a later approach. The inclusion, generally, has been pointed out as positive and the mechanisms for the exclusion were found in a lower degree in their attitude aspects comparing to the architectonic. In the latest, we identified the lack of conditions of access because no matter the school effort is through their adaptation situations, these ones are limited to the relative mobility by constructing ramps but the students' autonomy is weak because there are no adapted bathrooms, water fountains and telephone booths. The study allowed to discuss the body's role in the inclusion, suggesting new researches that come to continue the proposal of putting together the body, the inclusion and physical handicap.